Comparative assessment of Cucurbita moschata seed polypeptides toward the protection of human skin cells against oxidative stress-induced aging - Liu, Chunhuan; Wang, Peiyu; Yang, Cheng; Zhao, Bingtian; Sun, Peidong (Frontiers in Nutrition, 2023)
Skin aging problem has attracted much attention in current aging population society. Cucurbita moschata seed has a variety of potential biological activities in health food. However, few information is involved in skin anti-aging properties of Cucurbita moschata seed protein and its hydrolysate. We herein developed a novel strategy for protecting human skin cells against oxidative stress-induced aging by Cucurbita moschata seed polypeptides. Cucurbita moschata seed polypeptides (CSP) with different molecular weight distributions were successfully prepared by controlling protease hydrolysis time. The proportions of less than 1000 Da polypeptides of P-1, P-2 and P-3 were 0.11%, 20.26% and 92.72%, respectively. P-3 contained the highest proportion less than 1000 Da polypeptides, which was observed to promote human skin fibroblasts (HSF) growth by MTT assay, cell cycle and morphology. Interestingly, P-3 showed efficient repair effect on the H2O2-induced HSF cells, and inhibited the H2O2-induced aging of HSF cells. To explain this phenomenon, cell lifespan, intracellular ROS level, superoxide dismutase (SOD) activity and glutathione (GSH) content were investigated to reveal the interactions between P-3 and anti-aging. With the increasing of the P-3 concentration, ROS level significantly decreased, SOD activity and GSH content significantly increased in H2O2-induced HSF cells. These findings indicated that Cucurbita moschata seed hydrolysates showed potential to inhibit skin anti-aging, which could be advantageous in the health industry for producing personal care.